One Piece of the Jigsaw for the Cancer Recovery Strategy: Prevalence of COVID-19 in Patients With Cancer. (25th August 2020) - Moss, Charlotte; Dolly, Saoirse; Russell, Beth; Lei, Mary; Ghosh, Sharmista; Papa, Sophie; Sullivan, Richard; Van Hemelrijck, Mieke; Rigg, Anne; ,
COVID-19 has forced governments to make drastic changes to healthcare systems. To start making informed decisions about cancer care, we need to understand the scale of COVID-19 infection. Therefore, we introduced swab testing for patients visiting Guy's Cancer Centre. Our Centre is one of the largest UK Cancer Centers at the epicenter of the UK COVID-19 epidemic. The first COVID-19 positive cancer patient was reported on 29 February 2020. We analyzed data from 7-15 May 2020 for COVID-19 tests in our cancer patients. 2, 647 patients attended for outpatient, chemotherapy, or radiotherapy appointments. 654 were swabbed for COVID-19 (25%). Of those tested, 9 were positive for COVID-19 (1.38%) of which 7 were asymptomatic. Cancer service providers will need to understand their local cancer population prevalence. The absolute priority is that cancer patients have the confidence to attend hospitals and be reassured that they will be treated in a COVID-19 managed environment.